Even' Star organic farm - Nanni, Alfred J., (SAGE Knowledge. Cases., 2017)
This case describes a situation at an organic farm. The crops have been planted, but weather has affected the expected yields. A decision must be made about the profit-maximizing sales channels to choose given the unexpectedly limited output. The people, places, and quantitative data reflect actual observations, but some detail has been omitted or simplified for pedagogical purposes. The case was developed to integrate two academic disciplines: management accounting and quantitative methods. Once the technical aspects of the case analysis have been covered, class sessions have produced rich managerial discussions. The primary teaching objectives for this case are to explore distribution channel profitability from a differential analysis perspective and to introduce the concept of integer programming. Although the analyses can be complicated, the setting is a simple one that all students can readily visualize.